Job Satisfaction and Turnover Intention among Employees in Educity, Johor - Nur Dalilah Dahlan; Mohamad Firdaus Ahmad; Nur Syazwani Zulaikha Safwan; Nur Hani Syazwani Bakri; Ummi Kalthum Mohd Mokhtar (Information Management and Business Review, 2023)
Turnover among employees is a major issue that significantly has an impact on human resource management and organizational success. One of the key aspects of turnover is the loss of valuable knowledge and technical skills, which is particularly prominent in sports organizations. Thus, this study explored the relationship between job satisfaction and turnover intention in Educity, Johor. The research employed a quantitative design and involved distributing a questionnaire containing 40 items that assessed job satisfaction and turnover intention to 40 employees in Educity, Johor. The findings revealed a clear and negative association between job satisfaction and turnover intention. In other words, employees who are satisfied with their job are less likely to leave the organization. Consequently, the results of this study can be utilized to enhance employee well-being, guide future research, and inform human resource planning and development. It is recommended that policies be improved based on these findings, and further surveys should be conducted with a new sample.